A four-band and polarization-independent BDS-based tunable absorber with high refractive index sensitivity. Issue 47 (25th November 2021) - Wu, Xianglong; Zheng, Ying; Luo, Yao; Zhang, Jianguo; Yi, Zao; Wu, Xianwen; Cheng, Shubo; Yang, Wenxing; Yu, Yang; Wu, Pinghui
Abstract : We proposed a four-band terahertz tunable narrow-band perfect absorber based on bulk Dirac semi-metallic (BDS) metamaterials with microstructure. The resonance frequency of the absorber can be adjusted by adjusting the Fermi level of BDS. Abstract : A four-band terahertz tunable narrow-band perfect absorber based on a bulk Dirac semi-metallic (BDS) metamaterial with a microstructure is designed. The three-layer structure of this absorber from top to bottom is the Dirac semi-metallic layer, the dielectric layer and the metal reflector layer. Based on the Finite Element Method (FEM), we use the simulation software CST STUDIO SUITE to simulate the absorption characteristics of the designed absorber. The simulation results show that the absorption rate of the absorber is over 93% at frequencies of 1.22, 1.822, 2.148 and 2.476 THz, and three of them have achieved a perfect absorption rate of more than 95%. We use the localized surface plasmon resonance (LSPR), impedance matching and other theories to analyze its physical mechanism in detail. The influence of the geometric structure parameters of the absorber and the incident angle of electromagnetic waves on the absorption performance has also been studied in detail. Due to the rotational symmetry of the structure, the designed absorber has excellent polarization insensitivity. In addition, the maximum adjustable range of absorption frequency is 0.051 THz, which can be achieved by changing the Fermi energy of BDS. We also define the refractive index sensitivity ( S ), which is 39.1, 75.4, 119.1 and 122.0 GHz RIU −1 for the four absorption modes when the refractive index varies in the range of 1 to 1.9. This high-performance absorber has a very good development prospect in the frontier fields of bio-chemical sensing and special environmental detection.